Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s00276-011-0869-8
|View full text |Cite
|
Sign up to set email alerts
|

Translaminar screw fixation of the cervical spine in Asian population: feasibility and safety consideration based on computerized tomographic measurements

Abstract: Translaminar fixation using a 3.5 screw should be attempted with caution in Asian population. Pre-operative CT scan evaluation is mandatory before translaminar screw fixation is attempted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…17) in 2004 [70]. Since then, many authors have reported both the anatomical study and clinical application of this technique [71][72][73][74][75]. In this technique, screws are inserted into the lamina of C2 in a crossed trajectory and then connected with rods to C1 lateral mass screws, C1 pedicle screws, or even the C1 locking plate [29].…”
Section: C2 Translaminar Screwmentioning
confidence: 97%
“…17) in 2004 [70]. Since then, many authors have reported both the anatomical study and clinical application of this technique [71][72][73][74][75]. In this technique, screws are inserted into the lamina of C2 in a crossed trajectory and then connected with rods to C1 lateral mass screws, C1 pedicle screws, or even the C1 locking plate [29].…”
Section: C2 Translaminar Screwmentioning
confidence: 97%
“…This allows for the impromptu use of laminar screws as a salvage maneuver for C2 pedicle and pars screws even by experienced surgeons, or as a safety guard against errant screw placement by the occasional surgeon. As further advances in translaminar screws develop, including the lower cervical levels [1,4,16] where the canal is less capacious, modifications to our technique may help promote the safe placement of screws at these additional levels.…”
Section: Discussionmentioning
confidence: 99%
“…and they reported C4 and C5 never accepted bilateral translaminar screw, C3 and C6 accepted bilateral screws at low placement rates (8–24%), C7 accepted bilateral placement at a high rate (96% men, 84% women). However, a cadaveric study of 37 spines conducted by Yusof MI et al 25. showed that approximately 30, 17, 18, 49 and 100% of patients may receive translaminar screw fixation at C3–C7, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the sagittal plane, laminar height (LH) was measured as the height of the junction of the lamina and the spinous process (Fig. 2)132425. For unilateral placement, the thickness of lamina should be greater than 3.5-mm, and for placing the bilateral screws, we assumed a minimum required laminar height of 7 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation